Streptozotocin-induced mechanical hypernociception is not dependent on hyperglycemia - Cunha,J.M. (2009)
Since streptozotocin (STZ)-induced diabetes is a widely used model of painful diabetic neuropathy, the aim of the present study was to design a rational protocol to investigate whether the development of mechanical hypernociception induced by STZ depends exclusively on hyperglycemia. Male Wistar rats (180-200 g; N = 6-7 per group) received a single intravenous injection of STZ at three different doses (10, 20, or 40 mg/kg). Only the higher dose (40 mg/kg) induced a significant increase in blood glucose levels, glucose tolerance and deficiency in weight gain. However, all STZ-treated rats (hyperglycemic or not) developed persistent (for at least 20 days) and indistinguishable bilateral mechanical hypernociception that was not prevented by daily insulin treatment (2 IU twice a day, sc). Systemic morphine (2 mg/kg) but not local (intraplantar) morphine treatment (8 µg/paw) significantly inhibited the mechanical hypernociception induced by STZ (10 or 40 mg/kg). In addition, intraplantar injection of STZ at doses that did not cause hyperglycemia (30, 100 or 300 µg/paw) induced ipsilateral mechanical hypernociception for at least 8 h that was inhibited by local and systemic morphine treatment (8 µg/paw or 2 mg/kg, respectively), but not by dexamethasone (1 mg/kg, sc). The results of this study demonstrate that systemic administration of STZ induces mechanical hypernociception that does not depend on hyperglycemia and intraplantar STZ induces mechanical sensitization of primary sensory neurons responsive to local morphine treatment.